2018
DOI: 10.1016/bs.abr.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Xylem Ion Loading and Its Implications for Plant Abiotic Stress Tolerance

Abstract: Plant adaptive potential is critically dependent on efficient communication and coordination of resource allocation and signalling between above and below-ground plant parts. Control of xylem ion loading plays an important role in this process. This review focuses on the molecular identity, tissue-specific expression patterns, and transcriptional and posttranslational regulation of transporters mediating xylem loading of Na + , K + , and Clin plants grown under abiotic stress conditions such as drought, salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 195 publications
(218 reference statements)
1
10
0
Order By: Relevance
“…We have shown how a bioristor can dynamically monitor the physiological changes correlated with the regulation of the VPD and that the sensor response showed an opposite trend with VPD. The results achieved in this research paper supports in vivo the hypothesis that the reduction of the leaf transpiration rate in low VPD conditions leads to the accumulation of ions in the early phases of the plant response, followed by a decrease in ionic concentration due to re-opening of stomata under high VPD conditions [6,37,41,42]. During reversible transitions in VPD conditions we identified a clear and unique trend of the R signal, giving a direct and immediate response of the sensor from the inside of the plant system.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We have shown how a bioristor can dynamically monitor the physiological changes correlated with the regulation of the VPD and that the sensor response showed an opposite trend with VPD. The results achieved in this research paper supports in vivo the hypothesis that the reduction of the leaf transpiration rate in low VPD conditions leads to the accumulation of ions in the early phases of the plant response, followed by a decrease in ionic concentration due to re-opening of stomata under high VPD conditions [6,37,41,42]. During reversible transitions in VPD conditions we identified a clear and unique trend of the R signal, giving a direct and immediate response of the sensor from the inside of the plant system.…”
Section: Discussionsupporting
confidence: 79%
“…In low VPD conditions and low transpiration rate, the bioristor always responded with a rapid increase of the R value (2–4 dpi and 9–12 dpi; Figure 2), presumably because of the accumulation of electrolyte (mainly as Na + and K + ) [36,37] in the xylem sap as consequence of stomatal closure and the subsequent reduction of the transpiration stream [38].…”
Section: Resultsmentioning
confidence: 99%
“…Both active and passive transport systems are probably involved, but their respective roles may differ depending on the length of time since salinity onset. 249,250 Passive Na + loading is likely to be mediated by non-selective cation channels (NSCC). 251 Consideration of thermodynamics suggests, however, that under most physiologically relevant scenarios, xylem Na + loading should be an active process (see Shabala 250 for supporting arguments).…”
Section: Control Of Xylem Na + Loadingmentioning
confidence: 99%
“…Another important factor that affects the amount of Na 1 transport to the shoot is the rate of xylem Na 1 loading. The xylem Na 1 loading is thermodynamically active (Shabala, 2013) and is also mediated by either SOS1 or CCC transporters operating at the xylem parenchyma interface (Colmenero-Flores et al, 2007;Ishikawa et al, 2018). Here, we showed that transcript levels of SOS genes are significantly down-regulated in RNAi lines (Fig.…”
Section: Down-regulation Of Hvcam1 Enhances Salt Tolerance In Barleymentioning
confidence: 57%